2022
DOI: 10.3389/fcimb.2022.962283
|View full text |Cite
|
Sign up to set email alerts
|

Negative results of bronchoalveolar lavage fluid metagenomic next-generation sequencing in critically ill patients

Abstract: ObjectiveReports on negative results of metagenomic next-generation sequencing (mNGS) are scarce. We aimed to explore the diagnostic value of negative results in bronchoalveolar lavage fluid (BALF) mNGS and how to deal with the negative results in patients with severe respiratory disease.MethodsA retrospective analysis was performed on patients suspected severe community-acquired pneumonia who were admitted to the respiratory intensive care unit of the First Affiliated Hospital of Zhengzhou University from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In addition, considering the serious condition, we continued the empiric treatment for patients with negative results of mNGS. Despite the high sensitivity, negative results of mNGS can help to rule out pulmonary infection, but missed diagnoses may also exist [ 27 ]. In the face of negative results of mNGS, antibiotic de-escalation or discontinuation should be cautious, unless routine microbiological tests were also negative and patients were clinically improving without signs of active infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering the serious condition, we continued the empiric treatment for patients with negative results of mNGS. Despite the high sensitivity, negative results of mNGS can help to rule out pulmonary infection, but missed diagnoses may also exist [ 27 ]. In the face of negative results of mNGS, antibiotic de-escalation or discontinuation should be cautious, unless routine microbiological tests were also negative and patients were clinically improving without signs of active infection.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al. explored the clinical significance of negative results of BALF mNGS, demonstrated that negative results of mNGS can help to exclude infection ( Ma et al., 2022 ). Qian et al.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of infection remains important. Ma et al explored the clinical significance of negative results of BALF mNGS, demonstrated that negative results of mNGS can help to exclude infection (Ma et al, 2022). Qian et al evaluated the clinical value of negative mNGS results and found that when the mNGS test is negative, the negative prediction accuracy rate of the original specimen is significant (Qian et al, 2022).…”
Section: Smoking Related Ildmentioning
confidence: 99%
“…The content and time of report production needs consideration. Accurate organism identification is possible from sequencing <0.1% of the genome after a few minutes so there may be benefit producing organism profile or ''No (significant) organisms detected'' reports first [45]. Alternatively, clinicians may prefer waiting for a single report a few hours later that includes presence of specific resistance or virulence genes and predictions for phenotypic susceptibilities.…”
Section: Clinical Input To Refining Metagenomic Workflowsmentioning
confidence: 99%